PENERAPAN LEMBAR KERJA PESERTA DIDIK BERBASIS TPACK PADA MATA PELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR KELAS IV SDN 2 REDIN - Wahyu Kartiko; Arum Ratnaningsih; Titi Anjarini (STKIP Subang, 2025)
This study aims to determine the application of TPACK-based Student Worksheets(LKPD) in science and improve the learning outcomes of fourth-grade students at SDN 2Redin. TPACK-based LKPD is designed to integrate technological knowledge, pedagogy,and content to make learning more active, engaging, and tailored to student needs. Throughthis study, it is hoped that students will better understand the material on energytransformation while increasing their learning engagement in class.The research method used was Classroom Action Research (CAR), implemented intwo cycles. Each cycle included planning, action implementation, observation, andreflection, using TPACK-based LKPD. The study subjects were 16 fourth-grade students atSDN 2 Redin. Data collection techniques included observation of student activities, learningachievement tests, and activity documentation. The research instruments, multiple-choicequestions, observation sheets, and documentation, were analyzed descriptively. Dataanalysis techniques used were qualitative and quantitative analysis.The results showed: 1) The learning implementation in cycle I achieved an averageof 77.5% and in cycle II 90%. 2) The implementation of cycle I, the first meeting, had anaverage of 74 and the second meeting was 77. Then, cycle II, the first meeting was 80 andthe second meeting was 90. This proves that each meeting experienced an increase in theaverage value of students. The implementation of TACK-based LKPD can increase students'interest and learning outcomes.